Repair of a Perforated Sinus Membrane with a Subepithelial Palatal Conjunctive Flap: Technique Report and Evaluation - S. A. Gehrke; S. Taschieri; M. Del Fabbro; S. Corbella (Hindawi Limited, 2012)
The maxillary sinus grafting procedure has proven to be an acceptable modality for bone augmentation to provide a base for endosseous implants, routinely used for the rehabilitation of posterior maxilla. Perforation of the membrane is the most common complication in this type of procedure. This paper presents a technique for repairing a perforated Schneiderian membrane with a conjunctive connective tissue graft harvested from the palate and shows the histological and radiographic evaluation of the results. Ten consecutives cases with the occurrence of membrane perforation were included in this study. All were repaired with a flap of tissue removed from the palatine portion near to the surgical site. The technique is demonstrated through a clinical case. The results showed successful integration of 88.8% of the implants after 12 months from prosthesis installation. Histological evaluation of the samples showed that the use of nanocrystalized hydroxyapatite showed an adequate stimulation of boné neoformation within 6 months. Radiographic evaluation revealed a small apical implant bone loss, not compromising their anchorages and proservation. Thus, it can be concluded that the use of conjunctive technique with collected palate flap for sealing the perforation of the membrane of the sinus may have predictable result.